1979
DOI: 10.1128/aem.38.2.267-274.1979
|View full text |Cite
|
Sign up to set email alerts
|

Toxins of molds from decaying tomato fruit

Abstract: Among 27 mold isolates from decaying tomatoes, culture filtrates or ethyl acetate extracts of 8 isolates grown in yeast extract-sucrose medium were markedly toxic (mortality, >50%) to brine shrimp larvae. The toxicity of six of these isolates could be attributed to the presence of citrinin, tenuazonic acid, or T-2 toxin. Ethyl acetate extracts of five Alternaria isolates and one Fusarium isolate were mutagenic for Salmonella typhimurium strains. In ripe tomatoes inoculated with toxin-producing isolates and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 39 publications
0
25
1
Order By: Relevance
“…Alternaria spp. are prevalent ubiquitously appearing on the surface of cereals [2], vegetables [3] or fruits [4] as well as in the ground, on wood or walls. Exposure to Alternaria, especially Alternaria alternata has been associated with adverse health effects.…”
Section: Introductionmentioning
confidence: 99%
“…Alternaria spp. are prevalent ubiquitously appearing on the surface of cereals [2], vegetables [3] or fruits [4] as well as in the ground, on wood or walls. Exposure to Alternaria, especially Alternaria alternata has been associated with adverse health effects.…”
Section: Introductionmentioning
confidence: 99%
“…A. alternata has been demonstrated to produce some or all of these mycotoxins in various concentrations on tomatoes (17), sorghum (30), and pecans (31).…”
mentioning
confidence: 99%
“…Andersen and Frisvad [73] showed that P. tularense isolated from tomato fruit could produce janthitrems, paspalinine, paxilline, and 3-O-acetoxypaxilline. Harwig et al [74] have reported that P. expansum is capable of producing patulin and citrinin in tomato fruit. Our strain P. fluviserpens was also isolated from tomato fruit.…”
Section: Discussionmentioning
confidence: 99%